Implementation Of Digital Marketing In Construction Company In Renting Heavy Vehicles - Febrian Dayandri, Muhammad (Journal of Comprehensive Science, 2023)
This study focuses on how to implement digital marketing in heavy vehicle rental of a construction company, PT. Tussens Krida Utama (private company). this study uses qualitative methods with secondary data that are collected personally from PT. Tussens Krida Utama. The respondents of this study are managers and two employees. The methods used to collect data are direct observation and research on relevant documents. This study reveals that there are marketing ways that can be applied in a construction company that can contribute to significant income for the company, this is digital marketing. This study shows that the PT. Tussens Krida Utama has a high desire for digital marketing in order to develop the company.